Ճարտարապետության և քանդակագործության ներդաշնակ երկխոսություն… քանդակագործ Արա Սարգսյան - Հասմիկ Պարանյան (ՀՀ ԳԱԱ հրատ.)
В 1954-1955 годы в городе Ереван по проекту архитектора С. Сафаряна было построено здание президиума Национальной академии наук Армении. The building of the Presidency of the National Academy of Sciences of Armenia was constructed in Yerevan, 1954-55, designed by the architect S. Safaryan.
Keywords: Fine Arts; Architecture; Sculpture